Study the association between platelets count and grades of oesophageal varies in patients of cirrhosis of liver with portal hypertension - Priyadarshi, B. P.; Khan, Imran Kamal; Kumar, Vinay; Verma, Ashok Kumar; Midha, Tanu; ., Madhuri; Singh, Mahendra (International Journal of Advances in Medicine, 2020)
Background: cirrhosis of liver is a diffuse process of fibrosis that converts the liver architecture into structurally abnormal nodules Portal hypertension leads to dilatation of portal vein, splenomegaly, and formation of portal systemic collaterals at different sites. Screening endoscopy is recommended for early detection of esophageal varices (EVs) in cirrhotic patients with portal hypertension. However, this approach is limited by its invasiveness and cost. The aim of the study was to determine if platelet count can predict the presence of EVs, especially large (grade III, IV) EVs in need of prophylactic therapy. Methods: Statistically 100 patients previously or newly diagnosed with cirrhosis of liver with portal hypertension without history of hepatic encephalopathy, variceal bleeding, EVL, use of beta blockers, were selected for the study. Ultrasonography was performed in all cases to note the spleen size. Routine blood testing including platelet count was done and UGI-Endoscopy was done to detect presence of varices with grades. Statistical Analysis: Statistical analysis was done using Statistical Package for Social Survey (SPSS) for Windows version 17.0. The data obtained was analysed using mean, SD, Student’s t-test and chi square correlation coefficient, p value <0.05 was considered significant. Results: Among 100 patients studied ,90% patients were found to have esophageal varices. Based on endoscopic grading, incidence of grade 2 and grade 3 esophageal varices predominated, accounting to 48% and 23 % respectively. On correlation of platelet count with grades of esophageal varices it was evident that 44 patients had their platelet count less than 1 lac out of which 24 patients had grade 2 varices followed by 14 patients with grade 3 varices, p value <0.001 and was highly significant. Conclusions: The study depicts that with decrease in platelets count the chances of formation of higher grades of oesophageal varices increases and also a positive association exists.